Evaluasi Program CEBICOMM (The Class of Entrepreneurship Building and Innovative E-Commerce) di SMA Labschool UNESA - Lili Dwi Galuh Virnawati; Hazin, Mufarrihul (PT. Cahya Edupreneur Indonesia, 2023)
One way to improve programs and training is through evaluation. In this case the purpose of the evaluation activity is to know more about how to apply basic values in the educational process based on the vision and mission of education. SMA Labschool views entrepreneurship science as very interesting to be applied to students, therefore the entrepreneurship program can be used as a forum for creativity and innovation. The CIPP model is used in the evaluation of e-commerce-based entrepreneurial programs at SMA Labschool Surabaya. This research uses a descriptive type of research with a qualitative approach. Qualitative data is subjective because in this study it uses individual interpretation of existing phenomena by conducting field observations, interviews, and documentation. This program has been running well according to its goals since 2020 until now under the name CEBICOMM (The Class of Entrepreneurship Building and Innovative E-Commerce). Research findings show the CEBICOMM program is well managed by an entrepreneurial management team led by the curriculum waka. The obstacles so far are only about time. Student product marketing media usually uses E-Commerce and social media such as Whatsapp and Instagram. The social impact that is expected by this activity is that students have an entrepreneurial spirit. So making students not only have soft skills in the academic field but also have soft skills in the field of entrepreneurship as well. The products produced by students so far are mostly food and beverage products. The hope is that there will be P5 in this independent curriculum, the products produced and developed will not only be foods such as tempeh batik and other raw materials.